Extreme Daily Rainfall in Tarhuna: Causes and Impacts: تطرفات الأمطار اليومية (Journal of Humanitarian and Applied Sciences, 2026)
Tarhuna region has experienced a noticeable increase in extreme daily rainfall events under the influence of climate change, resulting in significant damage to resources and property. This study aims to identify extreme high daily rainfall amounts in the region, determine their causes, impacts, trends, and recurrence intervals.The study adopted a descriptive-analytical and quantitative approach, based on daily rainfall data obtained from NASA POWER (DAV) for the period 1980–2024. Field investigations were also conducted to document the resulting damages, supported by photographic evidence of affected sites.     The results confirmed the occurrence of significant extreme rainfall events, some of which recur at long intervals while others occur more frequently at shorter intervals. The study also revealed that these extremes have considerable impacts on natural and human resources, attributable both to the intensity of rainfall extremes and to limited public awareness and inadequate risk perception.The study recommends enhancing public awareness, adopting planning strategies that incorporate extreme rainfall values, and developing hazard maps to identify high-risk areas and prevent construction within them.
Keywords: Extreme Daily Rainfall; Recurrence Intervals; Climate Change; Tarhuna